2020
DOI: 10.3390/su12166655
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Forest on Slope Stability and Its Implications for Forest Management: A Case Study of Bailong River Basin, China

Abstract: Previous studies have shown that the mechanical effects of vegetation roots on slope stability can be classified as additional cohesion effects and anchorage effects. The present study investigated the combined mechanical effects (additional cohesion effects and anchorage effects) of vegetation on a slope with coarse-grained soil in the mountainous region (significantly prone to slope failure) of Gansu Province, China. A detailed survey of tree density, root system morphology and slope profiles was conducted, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…The upslope grown roots also provide good anchorage to the slope compared to roots on the downslope direction [57]. Wang et al [36] also showed that the additional cohesion provided by the roots was almost the same on different slope directions of the tree. Further, Genet et al [17] reported that a significant difference was not observed in RD measured in a different direction around the same tree.…”
Section: Roots Traits and Architectural Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The upslope grown roots also provide good anchorage to the slope compared to roots on the downslope direction [57]. Wang et al [36] also showed that the additional cohesion provided by the roots was almost the same on different slope directions of the tree. Further, Genet et al [17] reported that a significant difference was not observed in RD measured in a different direction around the same tree.…”
Section: Roots Traits and Architectural Indicesmentioning
confidence: 99%
“…Only those roots were considered, which were in the cross-sectional area (a × h (Figure 3b)), assuming all these roots play a role in providing additional root cohesion. If a root was branched inside the excavated area, the branched roots were not counted, as only the roots crossing the cross-sectional area (a × h) will play a role in root cohesion at that profile [36]. From these roots counting and roots diameter, the roots area (A r ) was calculated.…”
mentioning
confidence: 99%
“…Roots of the vegetation can reach up to the depths of 3m [4,7,9]. The zone of Soil with roots is represented in terms of root reinforced soil properties with anchors [8,10] and only as root reinforced soil [8].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the catastrophic consequence caused by slope failure, many reinforcement methods have been developed, such as drainage systems [7], stabilizing piles [8], reinforcement of vegetation, among others. Due to its environmentally friendly characteristics compared to soil nails, geosynthetics, retaining structures, gabions and shotcrete, the reinforcement of vegetation, such as grass and shrubs, on the slope stability, has been gradually recognized [9][10][11][12][13][14][15][16][17][18][19][20], and there are an increasing number of slope protection engineering with vegetation grew on the slope in recent years [19][20][21][22][23][24][25][26][27][28]. In fact, vegetation-soil interaction and plant-soil-atmosphere interaction are rather complex, thus the mechanism and effectiveness of vegetation reinforcement on slope stability are significant and it has attracted much attention of researchers.…”
Section: Introductionmentioning
confidence: 99%